Investigating Socioeconomic Disparities in the Potential Healthy Eating and Physical Activity Environments of Churches - Bernhart, John A. (Journal of religion and health, 2020)
Faith-based settings have the potential to improve health in underresourced communities, but little research has quantified and compared health-promoting elements in church environments. This study examines the number of potential indoor and outdoor physical activity opportunities, healthy eating opportunities, healthy living media, and total environmental resources present in churches (n = 54) in a rural, southeastern US county and the relationship between these resources and neighborhood income. In our sample, most churches offered potential indoor and outdoor opportunities for physical activity and healthy eating opportunities, with more variability in the number of healthy living media items on display compared to other environmental components. Common potential opportunities present in churches for physical activity included a fellowship hall and green/open space, while potential opportunities for healthy eating frequently included a refrigerator and sink. Compared to those in medium- and high-income neighborhoods, churches in low-income neighborhoods scored higher on measures of potential outdoor physical activity opportunities and lower on measures of total potential environment resources, healthy eating opportunities, healthy living media, and indoor physical activity opportunities, though only indoor physical activity opportunities reached statistical significance. Potential opportunities for using existing resources in and around churches for health promotion should be investigated further, particularly in rural areas.